(untitled) (Journal of Oriental Studies, 2016)
The article is dealing with Chinese position on Afghan problem and analyzing the ways of peaceful resolution. Also there are examined politic and economic interests of China in Central Asia and consequences of peaceful solution for Afghanistan and region.